TWO PUZZLES FOR MARQUIS’S CONSERVATIVE VIEW ON ABORTION1 - Card, Robert F. (Bioethics, 2006)
Don Marquis argues that abortion is morally wrong in most cases since it deprives the fetus of the value of its future. I criticize Marquis’s argument for the modified conservative view by adopting an argumentative strategy in which I work within his basic account: if it is granted that his fundamental idea is sound, what follows about the morality of abortion? I conclude that Marquis is faced with a dilemma: either his position must shift towards the extreme conservative view on which abortion is never morally permissible, or he must abandon any recognizably conservative view. This dilemma suggests that Marquis’s view is either deeply implausible or that he cannot use this argument to successfully support his preferred position.